2002
DOI: 10.1016/s0042-6989(02)00354-1
|View full text |Cite
|
Sign up to set email alerts
|

Reading with multiple preferred retinal loci: implications for training a more efficient reading strategy

Abstract: The reading strategies in individuals with central scotomas and more than one preferred retinal locus (PRL) were investigated using a scanning laser ophthalmoscope in order to understand the visual requirements that lead to the need to use more than one PRL during reading. It was found that: (1) PRL function can be deduced from variation in PRL usage for different size and length of isolated words; (2) each subject used two or more PRL to accomplish the functions of global viewing and discrimination, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 10 publications
4
70
0
5
Order By: Relevance
“…This finding may explain why reports on efficacy of eccentric-viewing training for reading are inconclusive and often contradictory. The retinal textmapping methodology may also demonstrate whether a subject has "multiple" tPRLs [7][8]. We did not find examples of multiple tPRLs in our study, but the simulations indicate that if a subject were to use multiple tPRLs our text-mapping methodology would demonstrate them.…”
Section: Discussionmentioning
confidence: 53%
“…This finding may explain why reports on efficacy of eccentric-viewing training for reading are inconclusive and often contradictory. The retinal textmapping methodology may also demonstrate whether a subject has "multiple" tPRLs [7][8]. We did not find examples of multiple tPRLs in our study, but the simulations indicate that if a subject were to use multiple tPRLs our text-mapping methodology would demonstrate them.…”
Section: Discussionmentioning
confidence: 53%
“…Guez et al also found that among their 24 patients, four had different PRLs depending on the size of the fixation target. Déruaz et al (2002) noted that patients could use multiple PRLs during reading for better performance. Déruaz et al made SLO recordings on five patients with central scotomata while the patients were reading words of different lengths and different character sizes.…”
Section: Multiple Prlsmentioning
confidence: 99%
“…Sample size Summary findings Déruaz et al (2002) 5 patients Mean diameter = 11 deg Guez et al (1993) 24 patients (40 eyes) Mean diameter = 10.3 deg Hassan et al (2002) 21 patients Mean diameter = 14.8 deg Schuchard et al (1999) 255 …”
Section: Studymentioning
confidence: 99%
“…Deruaz et al 5 determined that subjects use a combination of PRL types during reading by changing the character size and passage length and projecting a number of sentences (paragraphed) onto the retinal surface. Specifically, the subjects employ two types of PRL when reading, a global-viewing PRL, by which they take in an entire passage at once in the visual field, and a spatial-discrimination PRL, by which a discrimination function is employed to determine those parts of the passage that are hidden by the scotoma.…”
Section: Discussionmentioning
confidence: 99%